The Identities of Young America: A Case of American Exceptionalism and Emerging Identities in Letters from an American Farmer - Daryaee Motlagh, Ebrahim (Indonesian Journal of English Language Studies (IJELS), 2021)
This article is an attempt to examine the emerging identities and the primary examples of exceptionalism in early American literature by a review of excerpts from the "Letters from an American Farmer" written by J. Hector St. John de Crèvecoeur. To this end, after a brief introduction, exceptionalism is defined and explained as a political and ideological attitude. Then, a brief overview of pre-revolution and war literature is provided along with some prominent examples of literary works. Finally, after introducing the author’s work, the third letter of the above series entitled "What is an American?" is selected and analyzed within the theoretical framework of this article which addresses the emergence of American identity in early literary works. More specifically, the present article examines the American social life, emerging identities and the early signs of exceptionalism from Crèvecoeur’s perspective. As a conclusion, the analysis of selected excerpts shows that there are rudimentary elements and examples of this ideology in the case under study.